Retraction notice to: "The influence of ideological and political culture construction on students" psychological quality", HTS Teologiese Studies/Theological Studies 79(4), a8883 - Zhang, Ming (HTS teologiese studies, 2024)
Reason : The article ‘The influence of ideological and political culture construction on students’ psychological quality’ by Ming Zhang and Buzhou Guo has been retracted by AOSIS, as publisher, following an investigation undertaken by the publisher. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process. We cannot, therefore, vouch for the reliability or integrity of this article. Please note that this notice is intended solely to alert readers that the peer-review process of this article has been compromised. AOSIS regret that the usual quality checks did not identify these issues before publication and has since put additional measures in place to safeguard research integrity. The corresponding author, as the representative of all authors, has been given the opportunity to register their agreement or disagreement with this retraction. We have kept a record of any response received.